Human Capital dan Pertumbuhan Ekonomi: Studi Kasus Provinsi Jawa Tengah Tahun 2017-2023: Studi Kasus Provinsi Jawa Tengah Tahun 2017-2023 - Rohadatul Aisy; Sudarno Sudarno (Journal Of Business, Finance, and Economics (JBFE), 2026)
This study aims to analyze the effect of human capital through proxies of education (Gross Enrollment Ratio/GER), health (Life Expectancy/LE), and employment (Employment Rate/ER) on economic growth in Central Java Province during 2017-2023 period with Regional Gross Domestic Product (RGDP) at constant prices. This study uses quantitave descriptive analysis methods with a panel data regression model sourced from secondary data Statistics Indonesia (BPS). The results indicate that education has a positive but insignificant effect, health has a negative and insignificant effect, and employment has a positive and significant effect on economic growth. In contrast, all variables simultaneously demonstrate a positive and statistically significant impact on economic growth. Based on these results, the government is expected to stengthen labor policies that focus on increasing productivity while continuing to integrate education and health development to support sustainable economic growth. By focusing on integrated policies, efforts to improve human resource quality can become a long-term strategy to support an inclusive and sustainable economy. Therefore, synergy between the education, health, and employment sectors is necessary to achieve optimal results and benefit all levels of society.